Stochastic model predictive control: Insights and performance comparisons for linear systems. (23rd April 2018) - Seron, Maria M.; Goodwin, Graham C.; Carrasco, Diego S.
Summary: In this paper, we define several instances of model predictive control (MPC) for linear systems, including both deterministic and stochastic formulations. We show by explicit computation of the associated control laws that, under certain conditions, different formulations lead to identical results. This paper provides insights into the performance of stochastic MPC. Amongst other things, it shows that stochastic MPC and traditional MPC can give identical results in special cases. In cases where the solutions are different, we show that the explicit formulation of the problem can give insight into the performance gap.